PENGARUH POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Afifah; Khadijah; Nabila Azrina; Naena Suhailah; Rahma Adlya Zahra (Jurnal Humaniora & Sosial Sains, 2024)
Parenting plays a very significant role in children's social-emotional development. Supportive and responsive parenting can help children develop self-confidence, the ability to manage emotions, and good social skills. The main objective of this study is to explore the relationship between parenting and early childhood social emotional development. This research will use both qualitative and quantitative approaches through analysing data collected from interviews, questionnaires and observations. This research uses a descriptive case study approach to gain an in-depth understanding of the influence of parenting on early childhood social emotional development. Parenting has a very important role in shaping early childhood social-emotional development. In the context of this study, authoritative parenting, which emphasises a balance between strict control and emotional support, has been shown to contribute positively to children's well-being. Direct observations and questionnaire analyses revealed that parents who adopt authoritative parenting tend to create a supportive and safe environment for their children's development.